Penggunaan Strategi Manajemen Bakat Untuk Mempertahankan Generasi Milenial (Literatur Review) - Tini Utami; Retno Indriyati; Iik Suryati Azizah (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2025)
Talent management in the modern business sector is crucial because it provides a greater contribution to the management of human resources, which are now seen as valuable assets of the company. This approach not only functions as an internal strategy, but also as a form of anticipation of the risk of losing quality workers, considering the tendency of high employee mobility who can move to other companies at any time with more attractive offers. Through effective talent management, companies can optimize the potential of their personnel in achieving organizational goals. This study uses a literature study method, and the findings show that job satisfaction has a significant correlation with talent management practices. Some of the strategies identified in this context include developing digital skills, mapping talents in accordance with digital initiatives, creating a culture of innovation and maintenance, and utilizing technology and data analytics. A holistic and strategic talent management approach, supported by innovative leadership and adaptive marketing strategies, enables companies to effectively identify, develop, and retain the potential of individuals. This process includes the stages of recruitment, competency development, performance management, talent retention, and succession planning. The long-term output of successful talent management is the company's ability to retain the millennial generation workforce, which is known to be dynamic and demands a progressive work environment that supports continuous self-development